Interaction of finger enslaving and error compensation in multiple finger force production - Martin, Joel R; Latash, Mark L; Zatsiorsky, Vladimir M (Experimental brain research, 2009)
Previous studies have documented two patterns of finger interaction during multi-finger pressing tasks, enslaving and error compensation, which do not agree with each other. Enslaving is characterized by positive correlation between instructed (master) and non-instructed (slave) finger(s) while error compensation can be described as a pattern of negative correlation between master and slave fingers. We hypothesize that pattern of finger interaction, enslaving or compensation depends on the initial force level and the magnitude of the targeted force change. Subjects were instructed to press with four fingers (I index, M middle, R ring, and L little) from a specified initial force to target forces following a ramp target line. Force-force relations between master and each of three slave fingers were analyzed during the ramp phase of trials by calculating correlation coefficients within each master-slave pair and then two-factor ANOVA was performed to determine effect of initial force and force increase on the correlation coefficients. It was found that, as initial force increased, the value of the correlation coefficient decreased and in some cases became negative, i.e. the enslaving transformed into error compensation. Force increase magnitude had a smaller effect on the correlation coefficients. The observations support the hypothesis that the pattern of inter-finger interaction--enslaving or compensation--depends on the initial force level and, to a smaller degree, on the targeted magnitude of the force increase. They suggest that the controller views tasks with higher steady-state forces and smaller force changes as implying a requirement to avoid large changes in the total force.